FAKTOR-FAKTOR YANG MEMPENGARUHI KETAHANAN PANGAN RUMAH TANGGA PETANI DI KABUPATEN ACEH BARAT DAYA - Fadhiela.ND, Keumala; Faiza; Bagio (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
Apart from clothing and shelter, food is a basic human need for survival. Food security is often associated with meeting various food needs, such as safety and affordability. The aim of the study was to determine all variables that affect food security. This study involved all farmer households in Southwest Aceh District, with a sample of farmers who are members of food self-sufficient villages in the region. The sample size was 97 farmers from Blang Padang and Gunong Cut villages, both of which have large potential agricultural sectors. The study applied multiple linear regression analysis. Income level, rice price, and family dependents are some of the factors that affect food security. The results show that the food security condition of households in Aceh Barat Daya District is 90% food secure. This shows that farmers in Aceh Barat Daya District are able to fulfill their daily needs with their money. This is due to the fact that food is easily available and reasonably priced in the region, making it possible to achieve food security. The coefficient of determination of 0.733 indicates that 73.3% of the influence of the variables of opinion, number of household members, and household expenditure is the percentage of donation. Other variables that have not been included in the model used account for the remaining 26.7%. The F test results show that the factors tested jointly have a significant effect on the resilience of farmer households in Southwest Aceh District; partially, the number of family members, household expenditure, and rice expenditure have a significant effect at the 95 percent to 99 percent confidence level. The value of F count = 5.307 is greater than the value of F table = 2.49.   Keywords: Food Security, Food, Farmers, Food Expenditure Income